Significance of boulder shape, shoreline configuration and pre‐transport setting for the transport of boulders by tsunamis. Issue 9 (8th May 2020) - Oetjen, Jan; Engel, Max; Pudasaini, Shiva P.; Schuettrumpf, Holger
Abstract: Research on tsunami‐induced coarse‐clast transport is a field of rising interest since such deposits have been identified as useful proxies for extreme‐wave events (tsunamis, storm waves) that provide crucial information for coastal hazard assessment. Physical experiments are, beside in‐situ observations, the foundation of our understanding of how boulders are transported by tsunamis and provide clues to the development of empirical equations and numerical models describing the processes and fundamental mechanics. Nevertheless, investigating tsunami‐induced boulder transport is a comparatively young discipline and only a few experimental studies focusing on this topic have been published so far. To improve the knowledge on nearshore tsunami hydrodynamics, physical experiments utilizing real‐world boulder shapes have been carried out simulating three different shore types in a wave flume. Crucial insights were gained into boulder transport hydrodynamics and data resulting from the experiments were analysed in an empirical, statistical, quantitative and qualitative manner. The regular cuboid boulder – one of the specific shapes used in the experiments – showed the longest transport distances compared to a complex, natural boulder and a flat cuboid boulder, but also significant fluctuations regarding the total transport distance. The experiments indicate a strong influence of the shore shape on boulder transport behaviour. Experimental setups of increased mean transport distances also led to a higher spreading of results. This spreading was further amplified between the idealized‐shaped cuboid and the complex‐shaped boulder, which is associated with a lower drag coefficient. Due to the highly sensitive boulder reaction to divergent experimental setups, the need to recognize boundary conditions overcoming commonly considered parameters (e.g. roughness or Flatness Index) in field studies and numerical models is underlined. Beside the strong influence of initial boulder submergence and alignment, both the boulder shape and shore type influence the boulder transport pattern, increasing the total transport distance by more than 350% in some cases. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : Transport of coarse clasts (boulder) by tsunamis provides the opportunity to gain improved knowledge of nearhyphen;shore tsunami hydrodynamics and (pre‐)historical tsunami occurrences. Since the boulder transport is strongly controlled by the boulder shape and shore type, experimentally investigating transport patterns across a range of different shapes gives new and advanced insights in how their influences should be considered in future related studies.